Lysophosphatidic Acid Stimulates MCP-1 Secretion from C2C12 Myoblast - Tsukahara, Tamotsu (International Scholarly Research Network, 2012)
Chemokines are regulatory proteins that play an important role in muscle cell migration and proliferation. In this study, C2C12 cells treated with lysophosphatidic acid (LPA) showed an increase in endogenous monocyte chemotactic protein-1 (MCP-1) expression and secretion. LPA is a naturally occurring bioactive lysophospholipid with hormone- and growth-factor-like activities. LPA is produced by activated platelets, cytokine-stimulated leukocytes, and possibly by other cell types. However, the LPA analog cyclic phosphatidic acid (cPA) had no effect on the expression and secretion of MCP-1. LPA, although similar in structure to cPA, had potent inducing effects on MCP-1 expression in C2C12 cells. In this study, we showed that LPA enhanced MCP-1 mRNA expression and protein secretion in a dose-dependent manner. Taken together, these results suggest that LPA enhances MCP-1 secretion in C2C12 cells and thus may play an important role in cell proliferation.